Health-Related Problems and Drivers of Health-Related Quality of Life Among Community-Dwelling Older Adults - Watcharaporn Taburee; Supinda Sirilak; Rossukon Khotcharrat; Prattana Anekpunyakul; Piyameth Dilokthornsakul; Nada Lukkahatai; Chitima Boongird (SAGE Publishing, 2020)
Purpose: The aims of this study were to explore prevalence of health-related problems and identify factors associated with health-related quality of life (HRQOL) among community-dwelling older adults (CDOAs) in rural Thailand. Methods: A total of 384 CDOAs with mean age of 71 years (SD = 7.6) were recruited. The Thai Ministry of Public Health's comprehensive geriatric assessment (CGA) was used to measure the CDOAs' health conditions in the primary care unit of community hospitals. HRQOL of the participants was assessed by using the EQ-5D questionnaire. Results: The results showed that the most common health-related problems were risk of glaucoma (89.6%) and hypertension (64.6%). The HRQOL were predicted by the incidence of falls (β = −0.076, P < .001), Timed Up and Go Test (β = −0.087, P < .001), and age (β = −0.667, P = .002). Discussion: This study highlighted the need to incorporate CGA in family practice, which included risk of falls assessment by measuring TUG test, fall prevention, and to provide resources for caring older adults at home which ultimately will improve CDOAs' quality of life.